Effect of a 600 km ultra-cycling race on anthropometry in an elite female endurance cyclist - Knechtle, B.; Wirth, A.; Knechtle, P.; Kohler, G. (International Journal of Performance Analysis in Sport, 2009)
Prolonged physical endurance performances can show different effects on the organism in different genders. Systematic differences between men and women are still largely unknown. In this case study we describe the effects of a 600 km ultra-cycling race on the body composition in a female World class ultra-endurance cyclist. The athlete showed a decrease in fat mass and an increase in total body water and plasma volume. The increase in plasma volume presumably led to a haemodilution, which consequently resulted in an oedema and in an increase in total body water. Possible reasons are hypoproteinaemic oedema or an endocrine-induced renal retention of water in order to maintain metabolism processes for energy supply and blood flow during ultra-endurance performance. In the urinary proton magnetic resonance (1H-NMR) spectroscopy, however, we found no increase in ketone bodies. These findings in a single female cyclist should be further investigated in larger samples of male and female cyclists.